RANCANGAN PAKET WISATA PULAU TOMIA KABUPATEN WAKATOBI PROVINSI SULAWESI TENGGARA - Silfia Sartika Sari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Wakatobi Regency has a variety of natural resources, historical heritage, arts and culture as a tourist attraction. Wakatobi is synonymous with the four islands namely, Wangi-wangi, Kaledupa, Tomia, and Binongko. Tomia Island is an island that has many tourist attractions visited by tourists. Tomia Island has a complete tourist attraction ranging from natural and cultural tourism. This study aims to make Tomia Island Tour Packages based on the existing tourism potential on Tomia Island, Wakatobi Regency. This study uses a qualitative method with a descriptive approach. The subjects of this study were the Tourism and Creative Economy Office of Wakatobi Regency, the Heads of Tomia and East Tomia Sub-Districts, Tourism Managers and the Community. Data collection is done by document study, observation, interviews and documentation. The results showed that Tomia Island has natural and cultural tourism potential. Natural and cultural tourist attractions on Tomia Island are beaches, forts, Tomia Island dances, and Tomia Island folk games. Facilities on Tomia Island include communication facilities, transportation facilities, access roads, homestays, places to eat, places of worship, banks, health centers, and souvenirs. For the time in the tour package design is 4 days 3 nights with a price per person is IDR 2,297.000;-. Keyword : Tour Packages, Drafting, Tomia Island